GLOBAL LOGISTICS SYSTEMS - E., Georgieva; Abducul, Sh; E., Muratova, A.; R, Malikova; N, Dabiltaeva (Farabi Journal of Social Sciences, 2020)
Nowadays successful functioning in the foreign market is impossible without active application and continuous development of methods of the international marketing and tools of global logistics. This article is aimed at the study of the basic concept, importance and functions of globalization in the field of logistics. Consideration of the methodological and practical problems of building a global logistics systems on the basis of foreign experience. The article also reveals the main trends of globalization in the aspect of the use of logistics systems by transnational corporations and financial industrial groups. The purpose of this research is to study the features of the formation of global logistics systems and their application as a tool for local business to enter the world economy. The work is of high scientific and practical significance; the research presented in this article can be used in writing research papers, theses and master’s theses, and it can also be considered by business enterprises as recommendations for the application and continuous development of international marketing methods and global logistics tools. As a result of the study, the main trends in the development of global logistics systems were identified, and recommendations were made to optimize global logistics processes in terms of improving the quality of the international economy and its components.